Formulas for the velocity of Stoneley waves at the unbonded interface between two micropolar elastic half-spaces - Giang, Pham Thi Ha; Trung, Ngo Van; Vinh, Pham Chi (Vietnam Journal of Mechanics, 2025)
In this paper, we investigate the propagation of Stoneley waves along the unbonded interface between two micropolar elastic half-spaces. Using the complex function method, we derive explicit formulas for the wave velocity. These formulas have applications in various scientific fields, particularly in non-destructive evaluation. Two numerical examples illustrate how the obtained wave velocity formulas can be used to evaluate material parameters non-destructively.